Voltage-mode OTA-C multifunction biquadratic filter with four inputs and four outputs - Kumngern, Montree (My University, 2012)
This paper presents an electronically tunable versatile multifunction voltage-mode biquadratic filter with four inputs and four outputs employing six single-ended operational transconductance amplifiers and two grounded capacitors, which is very suitable for integrated circuit implementation. The proposed circuit can simultaneously realize low-pass, band-pass, high-pass, band-stop and all-pass voltage responses, without inverting-type input signal and component-matching condition requirements. The natural frequency and the quality factor can be orthogonally controlled. The active and passive sensitivities are low. PSPICE simulation results are given to confirm the presented theory. © 2012 IEEE.
Keywords: Analog signal processing; Biquadratic filter; Operational transconductance amplifier; Voltage-mode circuit